2017
DOI: 10.1177/0269215517705689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mirror therapy combined with neuromuscular electrical stimulation on motor recovery of lower limbs and walking ability of patients with stroke: a randomized controlled study

Abstract: Objective: To investigate the effectiveness of mirror therapy combined with neuromuscular electrical stimulation in promoting motor recovery of the lower limbs and walking ability in patients suffering from foot drop after stroke. Design: Randomized controlled study. Setting: Inpatient rehabilitation center of a teaching hospital. Subjects: Sixty-nine patients with foot drop. Intervention: Patients were randomly divided into three groups: control, mirror therapy, and mirror therapy + neuromuscular elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 36 publications
2
44
1
14
Order By: Relevance
“…28,29,32,[34][35][36][37][38][39][40] Two other studies reported no significant difference with MT, in outcomes measuring motor, sensory, and ADL components. 41,42 Only 4 studied the effects of MT on spasticity, out of which 3 reported no improvement as recorded on the Modified Ashworth scale 28,37,43 and one showed improvement on the Ashworth scale, 44 with 6 weeks of MT along with conventional rehabilitation. Sensory impairments were measured in 6 studies, and 4 report improved response to either noxious, tactile, or temperature stimuli.…”
Section: Application In Stroke Rehabilitation Motor -Upper Limbmentioning
confidence: 99%
See 4 more Smart Citations
“…28,29,32,[34][35][36][37][38][39][40] Two other studies reported no significant difference with MT, in outcomes measuring motor, sensory, and ADL components. 41,42 Only 4 studied the effects of MT on spasticity, out of which 3 reported no improvement as recorded on the Modified Ashworth scale 28,37,43 and one showed improvement on the Ashworth scale, 44 with 6 weeks of MT along with conventional rehabilitation. Sensory impairments were measured in 6 studies, and 4 report improved response to either noxious, tactile, or temperature stimuli.…”
Section: Application In Stroke Rehabilitation Motor -Upper Limbmentioning
confidence: 99%
“…32,40,45,47 Motor -Lower Limb/Gait/Balance Six studies reported on effects of MT on lower extremity impairment/function, gait, and balance. 33,39,43,[48][49][50] Records identified through database searching (n =3871) These studies showed improved motor recovery as recorded on Brunnstrom stages and improved lower extremity function through improved walking speed, single limb stance, step and stride lengths, static and dynamic balance, and decreased mediolateral and anteroposterior sway in standing. Two studies also reported a reduction in lower extremity impairment.…”
Section: Application In Stroke Rehabilitation Motor -Upper Limbmentioning
confidence: 99%
See 3 more Smart Citations